Mekanisme Pengelolaan Koin Nahdlatul Ulama dan Dampaknya pada Kesejahteraan Masyarakat Desa - Mursekha Mursekha; Nur Dian Islamiati (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
Nadlatul Ulama (NU) as one of the largest community organizations in Indonesia has a work program whose benefits can be felt by the wider community. One such program is the NU Coin Program. The NU Coin Program in Pekiringan Village, Talang District, Tegal Regency began to be implemented in early October 2020. The purpose of this research is to find out how the mechanism for managing the NU Coin Movement and its impact on the welfare of the people of Pekiringan Village, Talang District, Tegal Regency. This research is a type of qualitative research with a case study approach. Aspects that are used as operational indicators of variables in this study are income, population, health, education, consumption, and socio-culture. The results of the study stated that the management of Koin Nu was carried out by distributing 100 cans to NU residents of Pekringan village. Collection of NU Coins in the form of coins in denominations of Rp. 100, - Rp. 200, - to Rp. 500, - to Rp. 1000, - which is carried out from house to house by giving cans of NU Coinswhich is then collected once a month. The distribution of NU Coin funds has a positive impact on the welfare of the community, as shown by the majority of the people of Pekiringan Village being very helpful in meeting household needs both in material and spiritual terms, and the community is also greatly helped when there are religious activities.